KOMPOSIT ANTARA CNT DENGAN KITOSAN DENGAN PERBANDINGAN 1:3 - Masdania Zurairah (Journal of Innovation Research and Knowledge, 2024)
Research has been carried out between CNT and Chitosan in a ratio of 1:3 where the results obtained were CNT-Chitosan Nanocomposite (1:3). The results obtained showed that the particle size was 119 nm. The peak intensity is proportional to the graphitization of the CNT-Chitosan Nanocomposite 26.29o, 43.84o and 14.18o. The higher the weight ratio, the more the diffraction peak intensity will decrease. The addition of chitosan to CNT-Chitosan Nanocomposite 1:3 is able to remove impurities